Assessment of the competence formation in the field of protection and enforcement of intellectual property rights among teachers of higher education institutions by means of qualimetry. - Luniachek, V.; Nechuiviter, O.; Ruban, N. (Problems of Engineer-Pedagogical Education, 2021)
The paper analyses the materials of pedagogical research in which the qualimetric approach to assessing the development of certain competencies is considered. Particular attention is paid to the process of assessing the acquired skills and abilities in the field of protection and enforcement of intellectual property rights. The paper offers a factor-criterion model for assessing the competence formation in the field of protection and enforcement of intellectual property rights among the research and teaching staff of HEIs. The model is based on some factors, such as the ability to detect intellectual property in their own and students’ developments; ability to carry out patent research with the help of information technologies; ability to formalise intellectual property objects; ability to protect, defend and transfer intellectual property rights; ability to participate in the commercialisation of intellectual property. The paper presents the results of the assessment of competencies for the protection and enforcement of intellectual property rights acquired before and after the training conducted for the research and teaching staff on the basis of Ukrainian Engineering Pedagogics Academy. The effectiveness of the factor-criterion model "Assessment of the level of the competence formation of the scientific and pedagogical staff in the Free Economic Zone in the field of protection and enforcement of intellectual property rights" is confirmed by the methods of mathematical statistics.